2022
DOI: 10.1007/s40261-022-01205-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cannabidiol on Appetite and Body Weight: A Systematic Review

Abstract: Background and Objective Cannabidiol, one of the main components of the Cannabis sativa plant, is a non-psychotropic cannabinoid that has recently drawn the attention of researchers and clinicians for its potential therapeutic applications. In this systematic review, we aim to describe the possible effects of cannabidiol in appetite and body weight. Methods Both authors independently ran a thorough search in both PubMed and Cochrane databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
2
1
Order By: Relevance
“…As such, they produce distinct and sometimes opposing effects. For instance, Δ9-THC is widely accepted as orexogenic [ 91 ], whereas CBD is often associated with reduced appetite and weight loss [ 92 ]. To date, there is very little published data regarding the metabolic effects of individual cannabinoids.…”
Section: Discussionmentioning
confidence: 99%
“…As such, they produce distinct and sometimes opposing effects. For instance, Δ9-THC is widely accepted as orexogenic [ 91 ], whereas CBD is often associated with reduced appetite and weight loss [ 92 ]. To date, there is very little published data regarding the metabolic effects of individual cannabinoids.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported appetite changes as a treatment side effect rather than an advantage [ 36 38 , 40 , 41 ]. A recent systematic review investigating the effect of cannabis treatment on appetite and body weight suggested this treatment has an anorexigenic effect correlating with decreased body weight [ 57 ]. However, in our study, parents reported both increases and decreases in body weight and appetite.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the extent of the weight loss reversal might be a measure of treatment effectiveness. Data available from previous studies regarding the influence of CBD on body weight have indicated that CBD induces weight loss by appetite depression through CB2 receptors in rats [42], as well as in humans [43]. Nevertheless, the effect of oral CBD on body weight in mice was significant only for the highest daily dose of 615 mg/kg/day, while no weight change occurred after lower doses of CBD [44].…”
Section: Weight Lossmentioning
confidence: 96%